Peningkatan pH Saliva Perokok Aktif Menggunakan Permen Karet Xylitol - Asmalinda, Wita; Sapada, Edy; Agustin, Yeni (Poltekkes Kemenkes Tanjung Karang, 2021)
The Smoker active for a long time has an impact on decreasing the pH of the saliva. The most obvious impact is on cholinergic receptors in the brain which activates nerve action which results in a decrease in salivary gland secretion. The risk of decreased salivary function increases with the length of smoking and the number of cigarettes per day. The purpose of this study was to determine the effect of giving xylitol gum to increase salivary pH in active smokers. This type of research is an experimental clinical trial with a comparison group (pretest and posttest with control group design). This research was conducted at the Ibnu Sina Clinic in Palembang for 14 days, on 5-18 December 2020. The sample in this study were active smokers who met the inclusion and exclusion criteria. The number of samples is 52 respondents. The homogeneity of the sample characteristic data and measurement results was assessed by using the Kolmogorov-Simov test. Description analysis to determine the mean and standard deviation. There was a significant increase in the mean value of Saliva pH in the treatment group. It was concluded that xylitol gum affected on increasing the salivary pH of active smokers.